The Influence of Taxonomy and Environment on Leaf Trait Variation Along Tropical Abiotic Gradients - Oliveras, Imma; Bentley, Lisa; Fyllas, Nikolaos M.; Gvozdevaite, Agne; Shenkin, Alexander Frederick; Peprah, Theresa; Morandi, Paulo; Peixoto, Karine Silva; Boakye, Mickey; Adu-Bredu, Stephen; Schwantes Marimon, Beatriz; Marimon Junior, Ben Hur; et al. (Frontiers in Forests and Global Change, 2020)
Abstract Deconstructing functional trait variation and co-variation across a wide range of environmental conditions should increase the mechanistic understanding of community assembly processes and improve current parameterization of dynamic vegetation models. Here, we present a study that deconstructs leaf trait variation and co-variation to iithin-species, taxonomic-interspecific, and plot-environment components comparing three tropical environmental gradients in Peru, Brazil and Ghana. We measured photosynthetic, chemical and structural leaf traits using a standardized sampling protocol, totalling more than 1,000 individuals belonging to 367 species sampled. Variation associated with the whole interspecific taxonomic component (species+genus+family) for most traits was relatively consistent across environmental gradients, but intra-specificwithin-species variation and the plot-environment variation was strongly dependent on the environmental gradient. Trait-trait co-variation was also strongly linked to the environmental gradient where the traits were measured, although some traits had consistent co-variation components irrespective of environmental gradient. Our results demonstrate that filtering along gradients is mostly expressed through trait intra- and interspecifictaxonomic variation, but that trait co-variation is strongly dependent on the local environment, and thus global trait co-variation relationships might not always apply at smaller scales.